Answer:
Let's take this step by step:
2x+b=w
2x+b-b=w-b (the basics to what we are trying to do is to get x alone so that it equals whatever is on the other side of the equation.)
2x=w-b(now that we got rid of the b on the left side of the equation by canceling it out, we have to subtract by b on the other side of the equation as well)
2x divided by 2=w-b/2 (For our final step x is being mulitplied by 2 so what we can do to get x alone is canel out the multiplication by dividing by 2. What this does is it leaves x alone showing us what x equals)
x=w-b/2
Explanation: